HUBUNGAN KECEPATAN LARI 40 METER DAN KEKUATAN OTOT TUNGKAI DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA PUTRA KELAS VIII A SMP N 25 PEKANBARU - Yoga Andika; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations conducted in the field of research results squat style long jumps in male students of class VIII A PUTRA SMP N 25 Pekanbaru during the sports health physical education (PJOK) athletic program for long jump numbers that can be seen are still low, with student jump distance the average is 2.50 meters, while the KKM (minimum completeness criteria) in the long jump is 3.50 meters. This research was carried out in the SMP N 25 Pekanbaru field. Complete address is Jalan Kartama, Maharatu, Marpoyan Damai, Pekanbaru City, Riau. The time of this study was carried out after completing the proposal, on December 15, 2018, with a sample of 17 students. From the results of the study it can be concluded that there is a relation with 40 meters running speed and leg muscle strength with the results of squat style long jumps using the 40 meter running speed test three times the test, and taken more than three times this test, then do a strength test leg muscles using the Dynamomoter Kaki tool three times, and take the highest value, then test the results of the squat style long jump as much as three times the experiment, and take the furthest value to be used as data that will be processed by the researcher. The purpose of this study was to study the relationship of 40 meters running speed and leg muscle strength with the results of squat style long jumps on class VIII A boys in 25th Junior High School Pekanbaru.Key Words: Running Speed, Leg Muscle Strength, Squat Style Long Jump